2012
DOI: 10.1111/j.1601-5037.2012.00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oral health education on oral hygiene knowledge, practices, plaque control and gingival health of 13‐ to 15‐year‐old school children in Bangalore city

Abstract: Objectives To assess effectiveness of an oral health education (OHE) programme on oral hygiene knowledge, practices, plaque control and gingival health of 13‐ to 15‐year‐old school children in Bangalore city. Methods Three schools were randomly selected and assigned to experimental I, experimental II and control groups. At baseline, a 20‐item questionnaire was used to assess the oral hygiene knowledge and practices. Clinical examinations (Turesky–Gilmore–Glickman modification of Quigley Hein plaque index; Loe–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
90
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(102 citation statements)
references
References 18 publications
5
90
1
6
Order By: Relevance
“…This finding is not in agreement with results of observational studies presented in reference, which observed that the effective involvement of parents or other members of the family in educational intervention, may positively impact schoolchildren regarding oral health [15,27]. A hypothesis for this result may be due to the fact that parents did not support the proposal of researchers due to socioeconomic and cultural contexts that determine the oral health lifestyle and values for each family [27,28].…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…This finding is not in agreement with results of observational studies presented in reference, which observed that the effective involvement of parents or other members of the family in educational intervention, may positively impact schoolchildren regarding oral health [15,27]. A hypothesis for this result may be due to the fact that parents did not support the proposal of researchers due to socioeconomic and cultural contexts that determine the oral health lifestyle and values for each family [27,28].…”
Section: Discussioncontrasting
confidence: 57%
“…Other hypothesis for the lack of statistically significant difference in GBI and a not very evident difference in PI, as well as 2 in correct and wrong answers of groups IG1, IG2 and CG, may have been the impact of the educational methodology initially used in the three groups, which has been based on exercise of participation of children and use of educational resources that stimulate empathy of children to the subjects proposed, with the use of characters considered relevant to them and, therefore, different from interventions proposed in literature, which are primarily focused on cognitive contents of oral health, using illustrations and models meaningless to children and use of passive learning methodologies [2,13,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four of the studies used randomized controlled designs and provided adequate data for inclusion in the formal meta-analysis [10,12,15,18]. Three of the studies used plaque as one of their outcomes and only one used DMFT and DMFS index for assessing the oral hygiene status after conducting dental health education.…”
Section: Resultsmentioning
confidence: 99%
“…Ten articles were found to be relevant to the impact of school dental health education, and hence were included in the present review [9][10][11][12][13][14][15][16][17][18]. Data from all the 10 articles was critically analyzed to determine the impact and effectiveness of school dental health education programmes conducted in different parts of the country [Table/ Fig-2].…”
Section: Resultsmentioning
confidence: 99%